Rekonsiliasi dan Pemulihan Relasi dalam Perspektif Teologi Pengampunan: Tafsir Teologis Kejadian 50:15–21 - Tanuhendrata, Michael Sofian; Messakh, Jacob (Sekolah Agama Kristen Terpadu Pesat Salatiga, 2025)
The narrative of Genesis 50:15–21 describes the culmination of reconciliation in human relationships through Joseph's act of forgiveness towards his brothers. This story reveals a profound theological dimension of how God's love and sovereignty work amid human wounds and conflicts. In the modern context, especially in the digital age, human relationships are experiencing a crisis of empathy and a loss of spiritual meaning, necessitating a theological reconstruction of forgiveness as the basis for relationship restoration. The phenomenon of increasing digital dehumanisation and social breakdown emphasises the urgency of theological study of the biblical concept of forgiveness. The purpose of this study is to interpret Genesis 50:15–21 theologically to discover principles of reconciliation and relationship restoration that are relevant to character formation in contemporary Christian education. It uses qualitative research methods with a theological interpretation approach and literature study. It can be concluded that the narrative of Genesis 50:15–21 affirms forgiveness as an expression of God's love and sovereignty that restores human relationships damaged by sin and conflict. Joseph's reconciliation reflects a process of self-healing and relationship renewal rooted in faith and awareness of God's plan. Thus, the theology of forgiveness provides an ethical and spiritual foundation that is relevant for character building, Christian education, and relational ethics in a digital society that is increasingly losing its sense of humanity.AbstrakNarasi Kejadian 50:15–21 menggambarkan puncak rekonsiliasi dalam relasi manusia melalui tindakan pengampunan Yusuf terhadap saudara-saudaranya. Kisah ini menyingkap dimensi teologis yang mendalam tentang bagaimana kasih dan kedaulatan Allah bekerja di tengah luka dan konflik manusia. Dalam konteks modern, terutama di era digital relasi antar manusia mengalami krisis empati dan kehilangan makna spiritual, sehingga diperlukan rekonstruksi pemahaman teologis tentang pengampunan sebagai dasar pemulihan relasi. Fenomena meningkatnya dehumanisasi digital dan keretakan relasi sosial mempertegas urgensi kajian teologis terhadap konsep pengampunan dalam Alkitab. Tujuan penelitian ini adalah menafsirkan Kejadian 50:15–21 secara teologis untuk menemukan prinsip-prinsip rekonsiliasi dan pemulihan relasi yang relevan bagi pembentukan karakter dalam pendidikan Kristen kontemporer. Menggunakan metode penelitian kualitatif dengan pendekatan tafsir teologis dan studi pustaka. Dapat disimpulkan bahwa narasi Kejadian 50:15–21 menegaskan pengampunan sebagai penyataan kasih dan kedaulatan Allah yang memulihkan relasi manusia yang rusak oleh dosa dan konflik. Rekonsiliasi yang dilakukan Yusuf mencerminkan proses penyembuhan diri dan pembaruan relasi yang berakar pada iman dan kesadaran akan rencana ilahi. Dengan demikian, teologi pengampunan memberikan dasar etis dan spiritual yang relevan bagi pembentukan karakter, pendidikan Kristen, serta etika relasi di tengah masyarakat digital yang semakin kehilangan makna kemanusiaan.